THEORETICAL-METHODOLOGICAL FOUNDATIONS OF RESEARCH ON THE PROBLEMS OF DEMOCRACY IN HISTORICALPHILOSOPHICAL DISCOURSE - Yevheniya Ryabeka ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
An analysis of the approaches to defining the content and basic parameters of democracy should obviously begin with Aristotle's eminent ancient thinker. Analyzing Aristotle's work, we come to the conclusion that democracy is based on the middle class and a free market economy. A new stage in the understanding of democracy has to do with the achievements of modern day philosophers. J.-J. Rousseau writes in the paper "On the Social Treaty" that democracy is an instrument of ensuring the rights and freedoms of citizens and protecting minorities. Representatives of German classical philosophy made a fundamental contribution to the development of theories of democracy. In particular, in the writings of I. Kant we find the justification of the republican monarchy as a model of democracy in which the monarch obeys the will of the citizens. Ideally, these citizens should ideally be carriers of a disengaged mind, capable of philosophically formulating progressive ideas and demands for incumbent power. J. Fichte substantiated the approach according to which the people should take part in the state processes, and the authorities should ensure the implementation of the people's decisions: according to this approach, the will of the people is given a dominant importance, and the authorities are only trying to implement it. In Hegel's theoretical inheritance, an alternative view of democracy is upheld: the people are interpreted by the philosopher rather as a formless mass, and the fullness of power must belong to the monarch.